Estimating Demand Elasticities for Mobile Telecommunications in Austria - Ralf Dewenter; Justus Haucap (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2004)
This paper analyzes price elasticities in the Austrian market for mobile telecommunications services using data on firm specific tariffs. Both static and a dynamic panel data approaches lead to consistent results which provide evidence for a relatively elastic demand. Furthermore, some basic facts on the Austrian mobile telephone sector are presented.
urn:nbn:de:gbv:705-opus-16484
Keywords: L96; L13; C23; 330; Mobile telephony; Price elasticities; Unbalanced panel data; Dynamic panel analysis; Mobilkommunikation; Preiselastizität; Nachfrage; Schätzung; Österreich